2011
DOI: 10.1002/ceat.201100338
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Gas‐Particle Turbulent Flow in Spout‐Fluid Bed by Computational Fluid Dynamics with Discrete Element Method

Abstract: Gas and solid turbulent flow in a cylindrical spout-fluid bed with conical base were investigated by incorporating various gas-particle interaction models for two-way coupling simulation of discrete particle dynamics. The gas flow field was computed by a k-e two-equation turbulent model, the motion of solid particles was modeled by the discrete element method. Drag force, contact force, Saffman lift force, Magnus lift force and gravitational force acting on individual particles were considered in the mathemati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Moreover, the inter-particle contact forces resulting from the DEM approach are determined by the F C,ij force. The governing equations for forces are described elsewhere [14][15][16][17].…”
Section: Flow and Particle Transport Simulationmentioning
confidence: 99%
“…Moreover, the inter-particle contact forces resulting from the DEM approach are determined by the F C,ij force. The governing equations for forces are described elsewhere [14][15][16][17].…”
Section: Flow and Particle Transport Simulationmentioning
confidence: 99%
“…Since the development of the spout fluidized bed by Chatterjee (1970), a number of modifications were suggested to improve the bed performance. These modifications involve different geometrical configurations such as rectangular (Link et al, 2008), conical bottom (Zhong et al, 2006;Ren et al, 2011), slotted rectangular, multiple and elevated spout fluidized beds (van Buijtenen et al, 2011a(van Buijtenen et al, , 2012. One of the significant modifications includes insertion of a draft tube inside the bed, which results in an improved performance by restricting the lateral particle flow.…”
Section: Introductionmentioning
confidence: 99%
“…Tests with mixtures of glass beads of different diameters [23] in spouted beds have demonstrated that a higher proportion of the large-size component concentrates in the upper part of the bed. With respect to particles of the same size and different densities, Santos [24] observed that lighter particles concentrate at the top of the bed and near the wall, probably due the low elasticity of the collision between light particles [29,30].…”
Section: Experimental Segregation Profilementioning
confidence: 99%